The effect of coporate governance elements on corporate social responsibility (CSR) disclosure: An empirical evidence from listed companies at KSE Pakistan - Sadia Majeed; Tariq Aziz; Saba Saleem (International Journal of Financial Studies, 2015)
The purpose of this study is to investigate the potential effects of corporate governance (CG) elements on corporate social responsibility (CSR) disclosure. The annual reports of companies for the year 2007-2011 are examined to analyze the relationship between CG and CSR reporting. It considers the elements of CG such as board size, independent directors, foreign nationalities and women representation in the board, ownership concentration, institutional ownership, firm size and profitability. The multiple regression technique is used to measure the impact of CG elements on companies' CSR reporting. The results of the study demonstrate that overall CSR reporting by Pakistani companies are rather moderate however, the assortments of CSR items are really impressive. The study found positive and significant impact from board size, institutions ownership, ownership concentration and firm size on CSR reporting. The results also display contrary relationships between the women and foreign director's representation in the board and CSR reporting. This study suggests that organizations should audit their CG activities related to CSR in order to prove themselves good corporate citizens to all stakeholders.
Keywords: M14; G34; 330; corporate social responsibility; corporate governance; board size